2020
DOI: 10.3390/insects11080543
|View full text |Cite
|
Sign up to set email alerts
|

Functional Variation in Dipteran Gut Bacterial Communities in Relation to Their Diet, Life Cycle Stage and Habitat

Abstract: True flies and mosquitos (Diptera) live in habitats and consume diets that pose specific demands on their gut bacterial communities (GBCs). Due to diet specializations, dipterans may have highly diverse and species-specific GBCs. Dipterans are also confronted with changes in habitat and food sources over their lifetime, especially during life history processes (molting, metamorphosis). This may prevent the development of a constant species- or diet-specific GBC. Some dipterans are vectors of several human path… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 140 publications
(191 reference statements)
2
13
0
Order By: Relevance
“…Although there were no significant differences in alpha and beta-diversity measures between blood-fed and starved bed bugs, the number of bacterial species (the number of OTUs) was lower in blood-fed bed bugs than starved bed bugs (Table 1 ). The result is also similar to the study by Sontowski and Van Dam (2020) showed a blood meal in A. aegypti reduces the diversity and number of OTUs 34 .…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Although there were no significant differences in alpha and beta-diversity measures between blood-fed and starved bed bugs, the number of bacterial species (the number of OTUs) was lower in blood-fed bed bugs than starved bed bugs (Table 1 ). The result is also similar to the study by Sontowski and Van Dam (2020) showed a blood meal in A. aegypti reduces the diversity and number of OTUs 34 .…”
Section: Discussionsupporting
confidence: 91%
“…If the Pseudomonas was the contaminant, the loads from bed bugs under both blood-fed and starved states should be similar. Pseudomonas also could be found in many insects, including mosquitoes 34 , 50 , beetles 51 , and scolitines 52 , and always linked to detoxifying activities in insect's guts. Infections of Pseudomonas are beneficial in these cases, but targeted studies are needed to investigate Pseudomonas 's function in tropical bed bugs.…”
Section: Discussionmentioning
confidence: 99%
“…These bacterial taxa detected on insect eggs were also found in the gastrointestinal tracts of adults. The mechanisms by which this transference would occur are not yet elucidated, but one route of interest to our work involves adults transmitting symbionts by smearing fecal matter on the eggshells during oviposition ( Salem et al, 2015 ; Sontowski and van Dam, 2020 ). In the case of mosquitoes, this simple process would allow the larvae to acquire the bacteria shortly after hatching or even use them for their initial nurture ( Díaz-Nieto et al, 2016 ).…”
Section: Resultsmentioning
confidence: 99%
“…aegypti eggs ( Coon et al, 2014 ). It has been demonstrated that vertical transmission of microbes occurs mostly by egg-smearing, i.e., females impregnate the egg surface with symbiont-laden feces while ovipositing, allowing hatched larvae to acquire the symbionts ( Salem et al, 2015 ; Sontowski and van Dam, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…The presence of bacteria from the genera Ignatzschineria and Actinetobacter inhibits oviposition in BSFL, while the presence of certain Providencia species promotes this insect behavior (Zheng et al , 2013). Providencia has also been proposed to play a role in protein and lipid conversion in the BSFL gut (Ao et al , 2020) and to produce xylanases (Raj et al , 2013), which can assist the insect with the digestion of plant cell walls (Sontowski & van Dam, 2020). However, several members of this genera have also shown various degrees of virulence in fruit flies ( Drosophila melanogaster ) (Galac & Lazzaro, 2011).…”
Section: Discussionmentioning
confidence: 99%